Counsellor Competencies and Selected Issues in Canadian Counsellor Education - Jevne, Ronna (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to determine, from a comprehensive set of counsellor competencies, those for which there is a relatively high degree of consensus. Competencies were considered to include personal qualities, knowledge, and skills. A second purpose was to determine the degree of consensus with regard to specific issues in counsellor education, such as candidate selection, program content, counsellor educator qualifications, modes of training and directions for the future. A modified Delphi technique was used to gather data. A sample of 304 counsellor educators, counsellor supervisors, practicing counsellors, and counselling students across Canada responded to both phases of the questionnaire. Analysis of the data indicated a high degree of consensus relative to the various competency areas and specific competencies considered necessary for counselling effectiveness, similarly so for most issues pertaining to counsellor education programs. Implications of the results for the design of "Guidelines for Counsellor Education Programs in Canada" and for further research are presented.